Educating for Communion: Orthodox Responses to Pluralism and Extremism - IVANOV, Paul Bogdan (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
This study examines the challenges contemporary education faces in reconciling religious values within a globalized world characterized by individualism and extremism. The article explores how educational systems can maintain coherence while engaging with diverse perspectives and global influences, proposing pluralistic approaches that support critical thinking and intercultural encounter. Building upon the Ecumenical Patriarchate’s document For the Life of the World: Towards a Social Ethos of the Orthodox Church, the study highlights the Orthodox Church’s theological commitment to ecumenical engagement as a model for educational responses to religious diversity, grounding interfaith encounter in liturgical theology, Eucharistic communion, and the pursuit of peace. The study proposes that effective religious education in pluralistic contexts must be both confessional and intercultural, particular and universal, rooted in authentic tradition while capable of meaningful encounter with other traditions. Key Orthodox concepts such as theosis (deification), phronema (mind of the Church), kenosis (self-emptying), and philoxenia (hospitality) provide theological and pedagogical foundations for countering extremism and fostering genuine pluralistic engagement. The paper’s original contribution lies in applying Orthodox liturgical theology, specifically theosis, kenosis, philoxenia, and phronema, as a constructive normative framework for pluralist religious education, moving beyond mere tolerance towards a theologically grounded pedagogy of communion that advances further than existing secular or liberal pluralism models. By demonstrating that Orthodox liturgical practice functions as a formative pedagogy cultivating dispositions (kenotic openness, eucharistic solidarity, eschatological hope) directly applicable to pluralistic educational contexts, this study shows how strong religious identity and genuine pluralistic openness are not competing values but theologically unified in the Orthodox framework. The article concludes that the future of education in pluralistic societies depends on developing robust frameworks that balance fidelity to tradition with openness to intercultural encounter, grounded in positive visions of human flourishing, communal life, and divine communion.